Internal Migration, Crime, and Punishment in Contemporary China An inquiry into rural migrant offenders - Shen, Anqi (Springer Series on Asian Criminology and Criminal Justice Research,, 2018)
This work investigates inequality and social exclusion on contemporary Chinese society, specifically in the context of urbanization, migration and crime. Economic reforms started in the late 1970s (post-Mao) fuelled a trend of urbanization and mass migration within China, largely from rural areas to more economically developed urban regions. With this migration, came new challenges in a rapidly changing society. Researchers have extensively studied the rural-to-urban human movement, social changes, inequality and its impact on individuals and society as a whole. This volume provides a new perspective on this issue. It forges a link between internal migration, inequality, social exclusion and crime in the context of China, through qualitative research into the impact of this phenomenon on individuals' lives. Using a series of case studies drawn from interviews with inmates - men and women - in a large Chinese prison, it focuses on migrant offenders' subjective experiences, and analyses issues from the rarely-heard perspectives of migrant lawbreakers themselves. The research demonstrates how factors - including: the hukou system, rural-urban, class and gender inequalities, prejudices against rural migrants, and other structural problems - often lead to migrant offending. The author argues that to mitigate the effects of criminalisation, the root causes of these problems should be examined, emphasizing radical reforms to the hukou policy, cultural change in urban society to welcome newcomers, positive programs to integrate migrant workers into urban societies and improve their opportunities, rather than inflicting harsher penalties or reducing migration. While the research is based in China, it has clear implications for other regions of the world, which are experiencing similar tensions related to national and international migration. This work will be of interest to researchers in criminology and criminal justice, particularly with an interest in Asia, as well as those in related fields such as sociology, law and social justice.